2015
DOI: 10.1007/s11010-015-2378-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity and structural changes of human serum albumin from patients in advanced stages of diabetic nephropathy and the effect of the dialysis

Abstract: Changes in the antioxidant capacity of albumin and alterations of the albumin structural conformation were examined in patients in advanced stages of diabetes nephropathy. Human serum albumin was purified from diabetic patients in pre-dialysis (glomerular filtration rate [GFR] between 15 and 29 ml min(-1) 1.73 m(-2)) and those in dialysis (GFR ≤ 15 ml min(-1) 1.73 m(-2)) and then compared with albumin from patients with a normal GFR (>90 ml min(-1) m(-2)). We evaluated the antioxidant capacity of albumin using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…CRP of 3-10 mg/L suggests a high risk of AMI (Pearson et al, 2003). In addition to maintaining plasma osmotic pressure and acting as a carrier, albumin is also considered to be an important extracellular antioxidant (Kawai et al, 2018;Rosas-Diaz et al, 2015). The normal concentration of albumin may play an important role in inhibiting platelet activation and the apoptosis of vascular endothelial cells (Lam et al, 2013;Fernandez et al, 2019;Anraku et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…CRP of 3-10 mg/L suggests a high risk of AMI (Pearson et al, 2003). In addition to maintaining plasma osmotic pressure and acting as a carrier, albumin is also considered to be an important extracellular antioxidant (Kawai et al, 2018;Rosas-Diaz et al, 2015). The normal concentration of albumin may play an important role in inhibiting platelet activation and the apoptosis of vascular endothelial cells (Lam et al, 2013;Fernandez et al, 2019;Anraku et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of present study showed that, despite a moderate increase in albumin concentration after dialysis, the antioxidant capacity of plasma decreased. This indicates the effect of variation in the second structure by free radicals ( 22 ) that are effective in enhancing the antioxidant properties of molecules like proteins, and can be more valuable in comparison to concentration alone. Since hyperbilirubinemia is not an issue in the patients included in this study and proteins are nondialyzable molecules, we focus on uric acid and its correlations with the total antioxidant status assays, both before and after a HD session.…”
Section: Discussionmentioning
confidence: 99%
“…The gene transcription data presented in this study also demonstrated that MPO, EPX and LPO were also highly transcribed in the cultures, where rFab was determined to be oxidized. These genes are responsible for the production of hypohalous acids and hydroxy radicals from hydrogen peroxide in the presence of metal ions (Yan et al 2009;Filomeni et al 2015;Schieber and Chandel 2014;Yang and Butler 2000;Levine and Puzio-Kuter 2010;Lambeth 2004;Alfaro et al 2009;Garvey 2003;Zelko et al 2002;Kohler and Jenzer 1989;Davies 2011;Jong and Klebanoff 1980;Ten et al 1989;Oliver et al 2011;Rosas-Díaz et al 2015). The higher transcription of these genes suggests the presence of hypohalous acids and hydroxy radicals inside the CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…The gene transcription data also revealed the over transcription of some oxidative stress genes that are protective in nature: GSTP1, NCOA7, and ALB. The main function of these genes is to protect thiol containing proteins and lipids from oxidation by acting as a reducing agent and are not involved in reducing the level of H 2 O 2 found within the cells (Yan et al 2009;Filomeni et al 2015;Schieber and Chandel 2014;Levine and Puzio-Kuter 2010;Lambeth 2004;Alfaro et al 2009;Oliver et al 2011;Rosas-Díaz et al 2015). Finally, two oxidative stress protective or ROS-scavenging genes, GSS and TPO that remove or convert ROS to nonreactive oxygen species, were shown to be down regulated in bioreactor, where rFab was oxidized (Banerjee 2007;Li et al 2003;Ruf and Carayon 2006;Kessler et al 2008).…”
Section: Discussionmentioning
confidence: 99%